Two‐Dimensional Mg2Si Nanosheet‐Enabled Sustained Hydrogen Generation for Improved Repair and Regeneration of Deeply Burned Skin. Issue 10 (10th January 2023) - Zhu, Yanxia; Jiang, Qi; Jin, Zhaokui; Chen, Danyang; Xu, Qingqing; Chen, Jinchun; Zeng, Yue; Chen, Shengqiang; He, Qianjun
Abstract: Molecular hydrogen holds a high potential for wound healing owing to its anti‐inflammatory effect and high biosafety, but commonly used hydrogen administration routes hardly achieve the sustained supply of high‐dosage hydrogen, limiting hydrogen therapy efficacy. Here, two‐dimensional Mg2 Si nanosheet (MSN) is exploited as a super‐persistent hydrogen‐releasing nanomaterial with high biocompatibility, and the incorporation of MSN into the chitosan/hyaluronic acid hydrogel (MSN@CS/HA) is developed as a dressing to repair deeply burned skin. The MSN@CS/HA hydrogel dressing can continuously generate hydrogen molecules for about 1 week in the physiological conditions in support of local, long‐term, and plentiful hydrogen supply and remarkably promotes the healing and regeneration of deep second‐degree and third‐degree burn wounds without visible scar and toxic side effect. Mechanistically, a sustained supply of hydrogen molecules induces anti‐inflammatory M2 macrophage polarization in time by enhancing CCL2 (chemokine C‐C motif ligand 2) expression to promote angiogenesis and reduce fibrosis and also enhances the proliferation and migration capability of skin cells directly and indirectly by locally scavenging overexpressed reactive oxygen species, synergistically favoring wound repair. The proposed synthesis method, therapeutic strategy, and mechanisms will open a window for synthesizing a variety of MSene nanomaterials and developing their various proangiogenesis applications besides wound healing. Abstract : A hydrogen‐releasing hydrogel dressing based on two‐dimensional Mg2 Si nanosheets (MSN) is developed to achieve local, continuous, long‐term, and plentiful hydrogen supply at the burned site, remarkably promoting the healing and regeneration of serious burn wounds without leaving visible scars or inducing toxic side effects by enhancing the proliferation and migration of skin cells as well as anti‐inflammatory macrophage polarization‐mediated angiogenesis.